Extrapulmonary Tuberculosis masquerading as chest wall malignancy: Just never ceases to surprise! - Hussein, Mousa (IDCases, 2021)
With the emergence of the acquired immunodeficiency syndrome, we witnessed a higher incidence of disseminated and extrapulmonary tuberculosis. The infection sites commonly include lymph nodes, pleura, and osteoarticular areas, although any organ can be involved. Given the atypical presentation of the extrapulmonary disease, it poses a significant diagnostic challenge for the physicians; therefore, a high index of suspicion should be maintained, particularly where tuberculosis is endemic. Here we present a case of isolated chest wall tuberculosis in an immunocompetent patient.